Bất bình đẳng thu nhập giữa lao động có việc làm xanh và không có việc làm xanh - Hoàng Thị, Huệ; Nguyễn Hải, Anh; Phạm Ngọc, Toàn; Nguyễn Thu, Thảo; Nguyễn Hải, Nam; Nguyễn Cao Hà, Trang; Nguyễn Khánh, Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Vietnam has been implementing the National Green Growth Strategy over the period 2021–2030, in which promoting green jobs is a strategically important solution. However, the content and the measurement of green jobs in Vietnam have not been unified, so the paper proposes a method to identify and calculate green jobs in Vietnam according to The Occupational Information Network O*NET in the USA. Also, the study focuses on analyzing the income difference between green jobs and non-green jobs through the Labor Force Survey data over the period 2020–2022 to examine the income inequality between green jobs and non-green jobs. Besides, using the Blinder-Oaxaca decomposition method, the study shows that the group of individual characteristics and the group of labor and employment characteristics increase the income inequality between green jobs and non-green jobs, however, the opposite effect happens when it comes to geographical characteristics. According to the findings, the research proposes some recommendations such as the need to unify the definition and the identification method of green jobs as well as the need to develop a green job development and evaluation strategy for each industry, region, and the whole country, thereby, contributing to implementing the green growth strategy in the future.